2012 International Conference on Field-Programmable Technology 2012
DOI: 10.1109/fpt.2012.6412120
|View full text |Cite
|
Sign up to set email alerts
|

Parametric reconfigurable designs with Machine Learning Optimizer

Abstract: Abstract-We investigate the use of meta-heuristics and machine learning to automate reconfigurable application parameter optimization. The traditional approach involves two steps: (a) analyzing the application in order to create models and tools for exploration of the parameter space, and (b) exploring the parameter space using such tools. The proposed approach, called the Machine Learning Optimizer (MLO), involves a Particle Swarm Optimization (PSO) algorithm with an underlying surrogate fitness function mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Similarly to previous works, in [40], PSO is again improved with a learning model for parameter control, obtaining competitive performance compared to other parameter adaptation strategies. In [41], the hybridization of PSO, Gaussian process regression, and support vector machine is presented for real-time parameter tuning. The study concluded that hybridization offers superior performance compared to traditional approaches.…”
Section: Related Workmentioning
confidence: 99%
“…Similarly to previous works, in [40], PSO is again improved with a learning model for parameter control, obtaining competitive performance compared to other parameter adaptation strategies. In [41], the hybridization of PSO, Gaussian process regression, and support vector machine is presented for real-time parameter tuning. The study concluded that hybridization offers superior performance compared to traditional approaches.…”
Section: Related Workmentioning
confidence: 99%
“…[39], PSO is again enhanced with a learning model to control its parameters, obtaining a competitive performance compared to other parameter adaptation strategies. The manuscript [40] presents the hybridization between PSO, Gaussian Process Regression, and Support Vector Machine for real-time parameter adjustment. The study concluded that the hybrid offers superior performance compared to traditional approaches.…”
Section: Related Workmentioning
confidence: 99%
“…In [12] the authors investigate the use of advanced meta-heuristic techniques along with machine learning to automate the optimization of a reconfigurable application parameter set. The approach proposed in [12] is called the Machine Learning Optimizer (MLO), and involves a Particle Swarm Optimization (PSO) methodology along with an underlying surrogate fitness function model based on Support Vector Machines (SVM) and a Gaussian Process (GP). Their approach is mainly used to save time on analysis and application specific tool development.…”
Section: Related Workmentioning
confidence: 99%